FLOW PATTERNS IN THE SIBERIAN TRAPS DEDUCED FROM MAGNETIC FABRIC STUDIES - Callot J.-P.; Pozzi J.-P.; Gurevitch E.; Westphal M. (My University, 2004)
The Siberian traps rank among the largest flood basalt provinces in the world. Major magmatic activity is restricted to several short periods of less than 1 Myr around the Permo-Triassic boundary. We measured the anisotropy of magnetic susceptibility (AMS) of 183 basaltic samples from 28 individual lava flows belonging to the northwestern part of the flood basalt province, in order to test the reliability of such data in structural interpretation. These preliminary AMS data show a remarkably consistent pattern of magnetic lineations, that likely reflect the primary flow-related texture of the basalt. Our results also emphasize that AMS data are consistent with the well-documented petrological and geochronological data. The inferred flow directions are also consistent with flow directions expected from isopach maps. Our results suggest that the entire 2 km-thick lava pile was fed by fissure eruptions located in the rifted basin that bound the Siberian platform, and was controlled by topographical features, particularly major rift zones.
Keywords: anisotropy; lava flow; magnetic susceptibility; Siberian traps